2020
DOI: 10.1029/2019jd031817
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Impacts of Size‐Dependent Evaporation and Entrainment in a Global Model

Abstract: While most observations indicate well‐buffered clouds to aerosol perturbations, global models do not. Among the suggested mechanisms for this discrepancy is the models' lack of connections between cloud droplet size and two processes that can contribute to reduced cloudiness when droplets become more numerous and smaller: evaporation and entrainment. In this study, we explore different implementations of size‐dependent evaporation and entrainment in the global atmospheric model CAM5.3‐Oslo. We study their impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“…It may also be that the cloud adjustments to aerosols might be damped by other buffering processes (Stevens & Feingold, 2009), such as interactions with turbulence or entrainment. Recently, Karset et al (2020) linked drop number to turbulent entrainment in CAM5 and did not find significant sensitivity of ACI to parameterized turbulent entrainment. Further investigation of the interaction of turbulence and cloud macrophysics with aerosols is warranted, as cloud adjustments to aerosols and ACI in CAM6 do not seem sensitive to the microphysical representation of the warm rain process.…”
Section: Discussionmentioning
confidence: 99%
“…It may also be that the cloud adjustments to aerosols might be damped by other buffering processes (Stevens & Feingold, 2009), such as interactions with turbulence or entrainment. Recently, Karset et al (2020) linked drop number to turbulent entrainment in CAM5 and did not find significant sensitivity of ACI to parameterized turbulent entrainment. Further investigation of the interaction of turbulence and cloud macrophysics with aerosols is warranted, as cloud adjustments to aerosols and ACI in CAM6 do not seem sensitive to the microphysical representation of the warm rain process.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Karset et al. (2020) have added a size dependence to the parameterization of entrainment and evaporation and find a small impact on the radiative forcing due to aerosol‐cloud interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, there are also studies that implement more detail into parameterizations and find small effects. For example, Karset et al (2020) have added a size dependence to the parameterization of entrainment and evaporation and find a small impact on the radiative forcing due to aerosol-cloud interactions.…”
mentioning
confidence: 99%
“…In models with limited resolution, numerical diffusion leads to artificial mixing, perhaps great enough to drown out any parameterized microphysics–turbulence interaction that would represent the enhanced evaporation effect. For a given combination of model resolution and physics, the strength of the artificial mixing could give an indication of how parameterizable the aerosol‐enhanced evaporation effect is in that model (Karset et al., 2020; Sato et al., 2018). Indications are that Terai et al.…”
mentioning
confidence: 99%
“…In models with limited resolution, numerical diffusion leads to artificial mixing, perhaps great enough to drown out any parameterized microphysics-turbulence interaction that would represent the enhanced evaporation effect. For a given combination of model resolution and physics, the strength of the artificial mixing could give an indication of how parameterizable the aerosol-enhanced evaporation effect is in that model (Karset et al, 2020;Sato et al, 2018). Indications are that Terai et al (2020) have found a combination of resolution and physics that mitigates the numerical diffusion problem; quantifying the numerical diffusion in other combinations of resolution and turbulence scheme (be it ultraparameterization, higher-order closures, EDMF, or any other) could identify other viable combinations.…”
mentioning
confidence: 99%